Learning Apache Maven 3 - Bogahapitiya, Kapila; Safari eBooks ([Birmingham, U.K.] : Packt Pub., 2013)
"If you are a Java developer who wants to get started in Apache Maven and use it with a range of emergent and enterprise technologies including Struts2, Spring, Hibernate, and JAX-WS, then this video course is for you. No prior knowledge of Apache Maven is required to follow along with the examples.New! Packt Video courses: practical screencast-based tutorials that show you how to get the job done. Bite sized chunks, hands on instructions, and powerful results. This video course dives deep into the core concepts and terminologies of Apache Maven and enables you to get a firm grip on the basics in a step-by-step approach."--Resource description page.
Title from resource description page (Safari, viewed Jan. 27, 2014).
Presenter, Kapila Bogahapitiya.
Keywords: Application software -- Development; Project management -- Computer programs; Java (Computer program language); Apache (Computer file : Apache Group); Electronic books